Using Open Source Systems for Digital Libraries - Rhyno, Art (Libraries Unlimited, 2015)
Designed to ease the process of matching the community with the best content possible, this book provides a starting point for key technologies and the associated tools that make them usable. Introducing the concept of the digital library, Rhyno details the open source tools that are instrumental in developing many of the digital libraries in today's institutions, both from an introductory technical perspective and from the vantage point of the emerging community of users that is erecting the digital library.In a world of global networks and Internet time, digital libraries are becoming increasingly important in offering flexible, high-quality, and up-to-date resources to your patrons. Designed to ease the process of matching the community with the best content possible, this book provides a starting point for key technologies and the associated tools that make them usable. Introducing the concept of the digital library, Rhyno details the open source tools that are instrumental in developing many of the digital libraries in today's institutions, both from an introductory technical perspective and from the vantage point of the emerging community of users that is erecting the digital library.Rhyno gives special emphasis to the natural synergy between libraries and the Open Source movement, both of which are widely available to a community of users on a non-profit, publicly funded basis. The Internet itself is largely built on Open Source software, including the Sendmail mail server and the software that runs the Domain Name System (DNS), which locates network addresses.